2018
DOI: 10.1136/bmjopen-2018-022508
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic pain, anxiety, physical activity and mode of conception: a prospective cohort study of pregnant women

Abstract: ObjectivesPregnancy-related lumbopelvic pain (LPP) is a frequent condition known to significantly affect women in their daily life. The aetiology of pregnancy-related LPP pain is still not clearly established but the mode of conception has been suggested to contribute to LPP. Anxiety related to fertility treatments may be one of the contributing factors. The primary objectives of this study were to determine the evolution of LPP prevalence and severity, and anxiety throughout pregnancy in women who conceived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
(37 reference statements)
4
15
1
Order By: Relevance
“…In addition, despite the health benefits of regular physical activity during pregnancy, many women do not follow the recommended guidelines. Many studies indicate a decrease in the level of physical activity of pregnant women, this phenomenon was also observed in our study [57,58,59]. In our study, the vast majority of women (59.83%) described their physical activity as low, 36.94% as moderate, and 3.22% as high.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, despite the health benefits of regular physical activity during pregnancy, many women do not follow the recommended guidelines. Many studies indicate a decrease in the level of physical activity of pregnant women, this phenomenon was also observed in our study [57,58,59]. In our study, the vast majority of women (59.83%) described their physical activity as low, 36.94% as moderate, and 3.22% as high.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis was based on the fact that the former would experience more anxiety, especially fear to lose their baby, than the latter (Gourounti, 2016) and that greater anxiety would thereby result in lower PA practice among women who conceived after FT. However, our previous data revealed that anxiety levels were not different between women who conceived after FT and those who conceived naturally (Lardon et al, 2018), which could explain, at least in part, our result showing similar PA level in women, independently of their mode of conception. Nevertheless, our results are consistent with those of a prospective cohort study showing no difference in prenatal PA levels between women who conceived naturally (n = 295) and those who conceived after IVF (n = 297) (Fisher et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
“…Our result is still consistent with those reported in previous prospective and retrospective studies using subjective or objective measures of prenatal PA (Hayes et al, 2015, Hegaard et al, 2011, Owe et al, 2009). The decrease in PA levels over the course of pregnancy can be explained by different factors, such as the increase in physical discomforts and pelvic girdle pain as pregnancy progresses (Lardon et al, 2018, Owe et al, 2009). We were also expecting to find a greater decline in PA levels over the course of pregnancy in women who conceived after FT compared to those who conceived naturally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also explored the factors that hamper the maintenance of a sufficient physical activity level among pregnant women. Indeed, pregnant women were reported to often experience a repertoire of pregnancy-related symptoms, including lumbopelvic pain [13], psychological issues, such as anxiety and depression [14], and gestational weight gain [15], some of which would likely present a barrier for pregnant women to exhibit a higher level of physical activity [16,17]. Some pregnant women also indicated that a lack of time available for physical exercises, due to their busy work schedule, was also a contributing factor in their lack of physical activity [18].…”
Section: Introductionmentioning
confidence: 99%